Multiplex engineering and multifunction T cells for precise and effective immunotherapies - Jafarzadeh, Leila; Smaani, Ali; Delisle, Jean-Sébastien (Frontiers in Immunology, 2025)
Adoptive T cell transfer has emerged as a pillar of modern cancer immunotherapy. Propelled by viral and non-viral-based technologies, such as CRISPR-Cas9, genetic engineering offers novel opportunities for both emerging cellular therapies and the improvement of more established approaches such as chimeric antigen receptor (CAR) modified T cells. First-generation genetically modified T-cell therapeutics remain limited by the intrinsic constraints imposed by T-cell biology, such as T-cell exhaustion, poor trafficking into hostile tumor beds, toxicity, and challenges associated with tumor antigenic escape. Several of such limitations can be addressed by further engineering, expanding significantly the potential of cell therapy. This review focuses on the promise of using currently available cellular engineering technologies to genetically engineer single T cells at multiple different loci and/or confer several novel functions to circumvent the shortcomings of adoptive immunotherapy to treat cancer. Various methodologies and rationales for the design of these advanced engineered cellular products are described, along with emerging clinical data supporting the use of multiplex-engineered T cells. The limitations of advanced cell engineering and the remaining gaps that need to be filled to optimize the efficacy of adoptive T-cell immunotherapies are also discussed.